Role of miR-589-3p in human lumbar disc degeneration and its potential mechanism - Lu, Aiqing (Exp Ther Med, 2018)
The present study aimed to investigate the role of miR-589-3p in lumbar disc degeneration (LDD) and to explore the underlying mechanisms. Nucleus pulposus (NP) cells were stimulated with lipopolysaccharide (LPS) to simulate an in vitro model of intervertebral disc degeneration. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to detect the expression level of microRNA (miR)-589-3p in the NP cells, and the results demonstrated that the increased expression of miR-589-3p in LPS stimulated NP cells compared with the control. To further investigate the role of miR-589-3p in LDD, a human NP cell line with high/low miR-589-3p expression was generated using miR-589-3p mimics/inhibitors. In addition, a human NP cell inflammation model was conducted by LPS (10 µM) treatment. Western blot analysis and RT-qPCR were performed for detection of associated genes and proteins. Protein levels of pro-inflammatory factors, including tumor necrosis factor-α (TNF-α), interleukin (IL)-1β and IL-6 were evaluated by ELISA. Flow cytometry was used for cell apoptosis determination. Furthermore, Targetscan was used to predict potential targets of miR-589-3p, and a dual luciferase reporter assay was used to verify the prediction. The findings verified that miR-589-3p was significantly upregulated in LDD. In vitro, miR-589-3p mimics/inhibitors significantly increased/reduced the production of TNF-α, IL-1β and IL-6 in LPS stimulated NP cells. Furthermore, miR-589-3p mimics/inhibitors significantly promoted/inhibited LPS stimulated NP cell apoptosis. MiR-589-3p mimics/inhibitors significantly repressed/enhanced type II collagen and aggrecan expression in LPS stimulated NP cells. In addition, it was demonstrated that mothers against decapentaplegic homolog (Smad) 4 was a direct target gene of miR-589-3p, and was negatively regulated by miR-589-3p in NP cells. In conclusion, miR-589-3p may function as a promoter in LDD development via the regulation of Smad4.